PENGARUH PEMBERIAN EKSTRAK ETANOL JAHE MERAH (Zingiber Officinale Roxb var Rubrum) TERHADAP KUANTITAS DAN KUALITAS SPERMATOZOA MENCIT JANTAN (Mus musculus L.) YANG DIINDUKSI PARAQUAT DIKLORIDA - Dian Anggraini; Sutyarso Sutyarso; M. Kanedi; Hendri Busman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Paraquat is one of the chemicals that contributes to increasing pollution Indonesia. The careless use of paraquat can increase production of ROS (Reactive Oxygen Species), resulting in damage to a wide range of vital organs and reproductive system disorders such as infertility. ROS in the body can be captured by antioxidants. Red Ginger contains high antioxidants because there are active phenolic compounds such as gingerol, shagaol, zingeron, ginggerdiol, and zingibren which are proven to protect body cells from damage caused by ROS. This study was aimed to test the effectiveness of red ginger extract (Zingiber officinale Roxb. Var. Rubrum) on the quantity and quality of sperm in male mice (Mus musculus L.) induced by paraquat dichloride.This research uses a completely randomized design and is divided into six treatment groups with each four replications: K1 as the control group (only given H2O); K2 (paraquat induced a dose of 20 mg/kg Body Weight (BW) without the administration of the test substances); K3; K4; K5 (paraquat induced a dose of 20 mg/kg Body Weight (BW) and was given a red ginger extract at a dose of consecutive succession 6 mg / ml, 12 mg / ml, 18 mg / ml) and K6 (Only given a test material the red ginger extract as much as 18 mg / ml). Paraquat was given 2 times a week for 21 days and the red ginger extract was given for 35 days. The results of analysis by One-way ANOVA followed LSD at 5% significance level showed the ethanolic extract of red ginger can increase the sperm count, motility, viability and Morphology sperm of mice induced by the paraquat diklorida.